Business Strategies and Utilization of Tax Insentive Policies During the Covid-19 Pandemic and Implementation of Restrictions for Community Activities (PPKM) - Rd. Kusyeni; Ratih Kumala; Rd. Dancu Lokita Pramesti Dewi; Nadiah Abidin; Ryan Nugraha (Budapest International Research and Critics University, 2021)
After the normalization era of the pandemic (New Normal Era) in Indonesia with the new variant of the corona virus, the government issued a policy for the Enforcement of Community Activity Restrictions (PPKM) on the islands of Java and Bali, considering the number of corona virus sufferers is increasing. Enforcement of Community Activity Restrictions (PPKM) all activities are carried out online (online) to avoid community gatherings. Various policies were issued by the government to stabilize economic growth. To maintain State Finance revenue in terms of tax revenue, the government issued a new policy for SMEs and MSMEs considering that the contribution of SMEs and MSME business actors has quite potential. With this policy, what are the efforts and strategies carried out by the government and business people during the COVID-19 pandemic and the imposition of restrictions on community activities. This policy aims to maintain the business continuity of SMEs and SMEs, encourage public participation and knowledge of taxation. Qualitative data analysis techniques are carried out by collecting and analyzing data, and finally concluding the data. Based on the results of in-depth interviews with three respondents, the business strategy carried out by SME and MSME actors is in the form of product innovation, so that business opportunities can increase sales at online stores during the Covid-19 pandemic and the Enforcement of Restrictions on Community Activities. Tax incentive policies and SMEs and SMEs have taken advantage of these tax incentives and continue to improve compliance with tax obligations. SMEs players expect socialization and assistance to obtain more detailed information related to the latest tax regulations or policies.